Структура та властивості антифрикційних сплавів Fe-Cu-S після лазерної обробки - Марковський, Є.А.; Шатрава, О.П.; Олексенко, І.В.; Пелікан, О.А. (Physico-technological Institute of Metals and Alloys, 2023)
The object of research is the most promising antifriction alloys – gray cast iron, alloyed with copper and sulfur. It is noted that the use of copper as an alloying element in quantities exceeding its solubility in iron, allows to obtain in cast iron perlite-ferrite structure with inclusions of copper ε-phase. The article presents the results of a number of studies of laser thermal irradiation on the structure and properties of certain antifriction alloys. It is established that as a result of laser processing there is a significant increase in the concentration of alloying fusible elements in the surface layer of the samples in the area of laser exposure depending on the time of action of laser radiation. Structural phase analysis of the laser treatment zone, presented in the article, revealed a significant and positive effect of laser irradiation on the formation and distribution of phases. It was determined that starting from the processing speed V = 1.7 mm/s, a pronounced (80–120 mkm) hardening zone of the investigated alloys is observed on the surface of the samples. The paper presents data that indicate that in the vast majority of cases in the laser zone there is a significant (up to 1600 kg/mm2) increase in the microhardness of the main structural phase components of the experimental alloys. An analysis of the results of the wear test of the obtained samples is presented, which showed that with decreasing irradiation time, the intensity of their wear decreases, which is associated with an increase in the microhardness of the main phases on the surface in the treatment area. The positive effect of laser treatment on increasing the wear resistance of the studied experimental samples and friction pairs in general is also noted and the prospects of using this method of processing to improve the tribotechnical properties of iron-alloyed alloys of copper and sulfur are predicted.